Cerebral venous sinus thrombosis with venous hemorrhagic infarct in a patient with high-grade glioma of the left thalamus (Indian Journal of Case Reports, 2021)
Cerebral venous sinus thrombosis (CVST) is an uncommon type of venous thromboembolism whose diagnosis is often difficult due to its vague and non-specific clinical findings. Sometimes, the diagnosis is delayed as the symptoms were considered to be attributable to the underlying etiology, especially in patients with brain tumors such as high-grade glioma (HGG). We described the case of a 60-year-old male patient who presented with headache, generalized seizures, and right hemiparesis soon after receiving brain radiation and temozolomide therapy for HGG of the left thalamus. Initially, his symptoms were considered to be due to his underlying tumor but the subsequent imaging revealed left transverse, left sigmoid, and superior sagittal sinus thrombosis with venous hemorrhagic infarct of the left occipitoparietal lobe. The patient was started on anticoagulant therapy and symptoms resolved completely within a month. Clinicians should always consider CVST in the differential diagnosis of non-specific neurological symptoms, especially in patients with underlying brain tumors.